Voluntary simplicity: An exploration through text analysis. (19th January 2021) - Demirel, Apollo
Abstract: Overconsumption poses severe ethical problems and causes harm to the environment. Today many individuals change their consumption practices and actively limit their overall consumption due to ethical and environmental concerns. This article focuses on voluntary simplicity, a sustainable lifestyle phenomenon that comprises environment‐friendly consumption practices as an innate characteristic. This paper offers a fresh and nuanced understanding of voluntary simplicity through the lens of social cognitive theory (SCT) and by examining textual content generated by voluntary simplifiers on Facebook. Five thousand three hundred thirty‐six Facebook posts and comments were scrapped and examined using sentiment analysis, associative networks and cluster analysis. Results further our understanding of this lifestyle in the three interconnected domains of SCT (i.e., personal, behavioural and environmental). Insights obtained from this study can help develop a more complete conceptualization of voluntary simplicity and consumers who consider adopting this lifestyle choice.